2013
DOI: 10.3171/2012.10.peds12219
|View full text |Cite
|
Sign up to set email alerts
|

Choroid plexus papilloma and Pierpont syndrome

Abstract: The authors describe the case of a child who presented with hydrocephalus and phenotypic features characteristic of a multiple congenital anomalies/mental retardation syndrome. Dysmorphic facies, medial plantar lipomatosis, and developmental delay were observed in this case and are identical to documented findings of Pierpont syndrome diagnosed in 3 boys. This is the fourth case reported to date and is the first documented case of an oncological process— an intraventricular atypical choroid plexus papi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
(10 reference statements)
0
6
0
Order By: Relevance
“… 1 Two similar patients were subsequently reported, including one with a choroid plexus papilloma, whereupon the condition was named Pierpont syndrome. 2 3 While several patients resembling Pierpont syndrome have been reported, 4 clinical re-evaluation and molecular analyses have shown that they had either Coffin–Siris 5 or Wiedemann–Steiner syndrome (H. Brunner, personal communication 2013). Initially this caused uncertainty about the phenotype defining Pierpont syndrome, but the characteristics of both Wiedemann–Steiner syndrome and Coffin–Siris syndrome are better known nowadays and allow easy differentiation from the phenotype in the reported patients with Pierpont syndrome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 Two similar patients were subsequently reported, including one with a choroid plexus papilloma, whereupon the condition was named Pierpont syndrome. 2 3 While several patients resembling Pierpont syndrome have been reported, 4 clinical re-evaluation and molecular analyses have shown that they had either Coffin–Siris 5 or Wiedemann–Steiner syndrome (H. Brunner, personal communication 2013). Initially this caused uncertainty about the phenotype defining Pierpont syndrome, but the characteristics of both Wiedemann–Steiner syndrome and Coffin–Siris syndrome are better known nowadays and allow easy differentiation from the phenotype in the reported patients with Pierpont syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Initially this caused uncertainty about the phenotype defining Pierpont syndrome, but the characteristics of both Wiedemann–Steiner syndrome and Coffin–Siris syndrome are better known nowadays and allow easy differentiation from the phenotype in the reported patients with Pierpont syndrome. 2 3 Until now, the cause of Pierpont syndrome has remained unknown. However, de novo autosomal-dominant mutations were suspected to be the most likely cause.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, one patient has been described in literature with molecular and clinical Pierpont syndrome associated with an oncological process: an intraventricular choroid plexus papilloma (Vadivelu et al, ). It is the only case reported.…”
Section: Discussionmentioning
confidence: 99%
“…Several malformations are described in the literature, such as Arnold‐Chiari, microcornea, retinal coloboma, hernia, anal anomalies or cryptorchidism. Two other patients with a similar phenotype were subsequently reported, including a 6‐month‐old boy with a choroid plexus papilloma (Oudesluijs, Hordijk, Boon, Sijens, & Hennekam, ; Vadivelu, Edelman, Schneider, & Mittler, ). Burkitt‐Wrigth et al reported several patients resembling Pierpont syndrome, but clinical reevaluation and molecular analyses showed that they had either Coffin‐Siris or Wiedemann‐Steiner syndrome (Burkitt‐Wright et al, ).…”
Section: Introductionmentioning
confidence: 96%
“…The combined characteristics of plantar lipomatosis, unusual facies, and developmental delay are known as Pierpont syndrome [PS]. There have been a total of ten cases of PS reported since its initial description [ 1 3 ]. Key characteristics of the syndrome include neurodevelopmental delay, dysmorphic facial features, fat pads on feet and hands, and feeding difficulties.…”
Section: Introductionmentioning
confidence: 99%